2017
DOI: 10.1177/1744806916688902
|View full text |Cite
|
Sign up to set email alerts
|

A critical role of spinal Shank2 proteins in NMDA-induced pain hypersensitivity

Abstract: BackgroundSelf-injurious behaviors (SIBs) are devastating traits in autism spectrum disorder (ASD). Although deficits in pain sensation might be one of the contributing factors underlying the development of SIBs, the mechanisms have yet to be addressed. Recently, the Shank2 synaptic protein has been considered to be a key component in ASD, and mutations of SHANK2 gene induce the dysfunction of N-methyl-D-aspartate (NMDA) receptors, suggesting a link between Shank2 and NMDA receptors in ASD. Given that spinal N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The SHANK family of master scaffolding proteins include three members, that is SHANK1, 2 and 3. SHANK family proteins have been linked to Autistic Spectrum Disorder ( Lim et al, 1999 ; Mei et al, 2016 ; Monteiro and Feng, 2017 ; Yoon et al, 2017 ). Mutations in genes encoding SHANK family proteins (SHANK1, 2 and 3) often result in marked behavioural phenotypes in mice ( Mameza et al, 2013 ; Schmeisser et al, 2012 ; Won et al, 2012 ), such as an increase in repetitive routines, altered social behaviour and anxiety-like phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…The SHANK family of master scaffolding proteins include three members, that is SHANK1, 2 and 3. SHANK family proteins have been linked to Autistic Spectrum Disorder ( Lim et al, 1999 ; Mei et al, 2016 ; Monteiro and Feng, 2017 ; Yoon et al, 2017 ). Mutations in genes encoding SHANK family proteins (SHANK1, 2 and 3) often result in marked behavioural phenotypes in mice ( Mameza et al, 2013 ; Schmeisser et al, 2012 ; Won et al, 2012 ), such as an increase in repetitive routines, altered social behaviour and anxiety-like phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, studies on mice lacking Shank2 in the whole brain or specific cell types have further enhanced our understanding of the normal functions of Shank2 as well as ASDrelated pathophysiology (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). For example, mice lacking exons 6-7 and exon 7of Shank2 display autistic-like behavioral abnormalities that are associated with altered N-methyl-Daspartate receptor (NMDAR) function (37,38).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, depending on the acute or chronic phase and on the type of noxious stimulus, loss of Shank2 may result in increased or decreased sensitivity. Interestingly, Shank2-KO mice have been also reported to display a reduced sensitivity to the nociceptive response evoked by intrathecal injection of NMDA (Yoon et al, 2017). Since this procedure does not selectively activate one subpopulation of neurons, it is not possible to explain it in circuit terms.…”
Section: Discussionmentioning
confidence: 99%
“…Shank2-KO mice (obtained by targeting exon-6 and exon-7; Schmeisser et al, 2012;Won et al, 2012) display reduced social interaction, increased anxiety and compulsive grooming and are considered a bona fide mouse model of ASD. Recent work has suggested that Shank2-KO mice may display abnormal nociception due to alteration of spinal cord circuits (Yoon et al, 2017). Once again the neuronal subpopulations and the circuit architectural features responsible for such phenotype remain to be investigated.…”
Section: Introductionmentioning
confidence: 99%